2023
DOI: 10.4236/ijcm.2023.144014
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure Increases the Risk of Cerebral Microbleeds in Hypertensive Individuals

Abstract: Introduction: Hypertension is the leading preventable risk factor for major cardiovascular diseases worldwide. Recently, compelling evidence has emerged associating hypertension with cerebral microbleeds (CMBs), which are subclinical hemorrhages in the brain resulting from structural abnormalities in the small vessels that supply the brain. In addition to overall elevated blood pressure (BP), elevation in individual parameters such as systolic BP, diastolic BP, pulse pressure and mean arterial pressure could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…By analyzing all revealed significant risk factors of ESUS described above, it can be concluded that the vast majority of them could be the consequences of AH. For instance, it was demonstrated that AH is strongly associated with small vessel diseases that clinically manifest as brain changes (cerebral microbleeds, brain atrophy, and the others) and cognitive deterioration that were found in our research [29][30][31][32]. It is also well known that AH may be the leading cause (however, not the only one) of the increased heart rate [33,34], conduction disturbance, elevated PASP [35], and heart atrial and ventricular remodeling [36][37][38], all of which were identified in ESUS patients in the current study.…”
Section: Discussionsupporting
confidence: 67%
“…By analyzing all revealed significant risk factors of ESUS described above, it can be concluded that the vast majority of them could be the consequences of AH. For instance, it was demonstrated that AH is strongly associated with small vessel diseases that clinically manifest as brain changes (cerebral microbleeds, brain atrophy, and the others) and cognitive deterioration that were found in our research [29][30][31][32]. It is also well known that AH may be the leading cause (however, not the only one) of the increased heart rate [33,34], conduction disturbance, elevated PASP [35], and heart atrial and ventricular remodeling [36][37][38], all of which were identified in ESUS patients in the current study.…”
Section: Discussionsupporting
confidence: 67%